Corrective Feedback on Pronunciation Errors: Teacher’s Perception and EFL High School Students’ Self-Reflection - Rafki Okta Arianto (Journal of English Education and Teaching, 2019)
This study aimed to find out whether there is any effect of peer feedback through instagram on student’s writing recount text at the tenth grade students of SMA 4 Rejang Lebong. Quasi-experimental design, since two classes are taken as the sample of the study with 36 students X IPA 1 and 34 students X IPA 3. Which class experimental class and a controlled class. The experimental class is taught by doing peer feedback through instagram while the controlled class do not. Moreover, this research is conducted through the following procedures; pretest, treatments, and post-test. The data analyzed is gained through writing test. There was significant different between the students who taught by peer feedback through instagram and those who were taught by conventional teaching. It can be seen from the post-test result. The mean score in experimen class was 75,67 and the mean score in control class was 67,38. From the result of t tesr was obtained 3,03 while t table was 1,67. It was proved that t test obtained was higher than t table (3,03>1,67) which the null hypothesis (H0) is rejected and the hypothesis (H1) is accepted. Finally, it can be concluded that peer feedback through instagram is effective toward students’ writing ability in Recount text.